WAYS TO CREATE A HEALTHY LIFESTYLE IN THE FAMILY - Abdilaxatov Zafar Abdigapirovich (Web of Journals Publishing, 2025)
This article explores effective strategies for fostering a healthy lifestyle within the family setting. It emphasizes the importance of balanced nutrition, regular physical activity, mental well-being, and positive communication habits. The study highlights how consistent routines, mutual support, and shared goals contribute to long-term health benefits for all family members. Special attention is given to the role of parents as role models and the influence of home environments on children's habits and development.
Keywords: Healthy lifestyle, family health, nutrition, physical activity, mental well-being, parenting, habits, well-being, communication, role modeling.